Analisis model pengelolaan zakat dan wakaf (Studi Yayasan Yatim Mandiri Cabang Malang) - Solekah, Nihayatu Aslamatis (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
Among the objectives of waqaf in islam is the distribution of welfare among the people and povertyÂ  eradication. When well managed endowments will support Â the development both in economic, religious, social, cultural, political, defense and scurity. The purpose of this study was to examine the management model of zakat and waqf productive. The result of this study are expected to provide benefits to provide a more substantial to the scientists, researchers, readers and the public that there is a model of productive management of waqf grant that can be used as an example in the management of zakat and waqf productive. The result showed that the foundation is independent orphans have an independent organizational system, in which the form of institutions such as the institute amil zakat generally resulting in organizational system there is no interfence from goverment regulations. Constraints/ problems experienced in Yayasan Yatim Mandiri Malang from the internal aspect is the lack qualified Human Resources an Human Resource Capibility less creative. Constraints/ problems faced in the Orphan Foundation of Malang independent external aspect is still modest community thought lack of support from family. To resolve the internal problems of orphans independent foundation that is to prepare a Qualified Human Resource (Internal). As for the external problem than it should maximize the marketing and provide understanding to families or orphans